2023
DOI: 10.1088/2053-1591/acc82f
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the PBF-LB/M processing of the Al-Si-Cu-Mg composition through the use of pre-alloyed powder

Abstract: Among the many additive manufacturing technologies for metals, Powder Bed Fusion-Laser Beam (PBF-LB\M) stands out for its capacity to produce complex-shaped functional parts. However, the PBF-LB\M materials portfolio is still limited and the research into new high-performance Al-based alloys is ongoing. The improved properties with the addition of 4 wt% Cu to the AlSi10Mg alloy have been previously investigated in the literature through the in-situ alloying approach in which the starting powders of Cu and AlSi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Furthermore, the study conducted on the AlSi10Cu8Mg revealed a mean hardness value of ca. 190 HV, a 22% higher value compared to those published in previous works by Martin et al and Martucci et al with the AlSi10Cu4Mg system [21,22]. The positive preliminary results obtained with the AlSi10Cu8Mg alloy pave the way for Al-Si-Cu-Mg alloys with higher copper content studies.…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations
“…Furthermore, the study conducted on the AlSi10Cu8Mg revealed a mean hardness value of ca. 190 HV, a 22% higher value compared to those published in previous works by Martin et al and Martucci et al with the AlSi10Cu4Mg system [21,22]. The positive preliminary results obtained with the AlSi10Cu8Mg alloy pave the way for Al-Si-Cu-Mg alloys with higher copper content studies.…”
Section: Introductionmentioning
confidence: 53%
“…The EDS results, reported in Figure 3, clearly demonstrate that the brighter areas revealed by the SEM investigation were enriched in Cu, and the darker ones in Si. Based on the literature related to similar compositions, it is reasonable to assume that the matrix is the α-Al phase and the network is composed of the Al-Si eutectic and the Al 2 Cu phase [21,22,39]. The microstructures of the AlSi10Cu4Mg and AlSi10Cu8Mg systems appear morphologically comparable, but by applying contrast image analysis with ImageJ software, it was possible to assess a fraction of Al 2 Cu-rich areas in the AlSi10Cu8Mg that was 7% higher than in the AlSi10Cu4Mg.…”
Section: Powders Assessment: Morphology and Chemistrymentioning
confidence: 99%
See 2 more Smart Citations